Analysis of Renewall Readiness for Quality Management System Certification Based on ISO 9001:2015 Using Gap Analysis - Tarigan, Uni Pratama Pebrina; Rajagukguk, Dameria (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2023)
PT PI is a company engaged in Port Services. PI still follows the company's regulations that are still set to date, namely the implementation of the Quality Management System 9001:2008, but the Quality Management System has ended in 2020. Therefore, PT PI must adjust the Quality Management System to the latest standards of Quality Management System ISO 9001: 2015 in order to maintain the quality of Service Quality in the company. The purpose of this study is to determine the readiness in the implementation of Quality Management System ISO 9001:2015 in obtaining certification. The method used in this study is Gap Analysis. Gap Analysis is a measurement method to determine the gap (Gap) by mapping the current Quality Management System and comparing it with the requirements of the ISO 9001:2015 Quality Management System, so that the analysis of differences from the Quality Management System at PI is now with the requirements of the ISO 9001:2015 Quality Management System to be determined.